THE SIYASAH SHAR'IYYAH PERSPECTIVE OF NAJIB'S TRANSFORMATIONAL AGENDA IN MAKING MALAYSIA INTO A HIGH INCOME NATION - Lukman Thaib (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
Malaysia is a country that since its independence has endeavored to practice democratic governance. In line with this, it seeks to ensure that the Malaysian government is representative of the will of the people. To achieve this, there must be in place numerous mechanisms to ensure accountability and transparency while also ensuring that it has an